2019
DOI: 10.1080/14719037.2019.1619808
|View full text |Cite
|
Sign up to set email alerts
|

What matters to me! User conceptions of value in specialist cancer care

Abstract: This paper is the first to apply the services marketing framework of service-dominant logic (S-D logic) to enhance understanding of patient conceptualisations of value in the context of cancer health services. Using data from a case study, the findings reveal that 'value' is a temporal, experiential, and complex concept. Three dominant themes are identified as contributing to value creation; access to resources, quality of interactions, and resource use.Although these findings show a broad degree of support fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…Top left in figure-2 are emotional-cognitive individuals, who from practice are learning from the exercise of discretion possible in the locale, guided by emotional attachments to design and deliver service models that solve users' problems. Organizing is a systems level; it assumes the practice in the system of individual users (and individual other agents) and as Hardyman, Kitchener, and Daunt (2019) note, that as agents respond to the results of practice, new patterns of practice will emerge, referencing (in healthcare) professional and clinical standards. Since users can be vulnerable and depend upon service outcomes for wellbeing, these combine control (standards) and trust (shared intent).…”
Section: Social Learning Governance and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Top left in figure-2 are emotional-cognitive individuals, who from practice are learning from the exercise of discretion possible in the locale, guided by emotional attachments to design and deliver service models that solve users' problems. Organizing is a systems level; it assumes the practice in the system of individual users (and individual other agents) and as Hardyman, Kitchener, and Daunt (2019) note, that as agents respond to the results of practice, new patterns of practice will emerge, referencing (in healthcare) professional and clinical standards. Since users can be vulnerable and depend upon service outcomes for wellbeing, these combine control (standards) and trust (shared intent).…”
Section: Social Learning Governance and Frameworkmentioning
confidence: 99%
“…Our paper features recent PMR research on value creation and value destruction: Bozeman (2018), Hardyman, Kitchener, and Daunt (2019), Trishchler, Dietrich, and Rundel-Thiele (2019), Dudau, Glennon, and Verschuere (2019) and Engen et al (2020;Plé, Chumpitaz Cáceres, and Harris (2010). These papers are not directly concerned with governance; they focus on coproduction from service-dominant logic marketing perspective and investigate how and why value creation and/or destruction occurs.…”
mentioning
confidence: 99%
“…The last three papers in this special issue help us understand this paradigm in action as well as open the way to future research pathways towards a post-public service logic paradigm. To start with, Hardyman and colleagues (Hardyman et al 2019) apply SDL to a public service context to explore what value means for users of specialist cancer care services. Antecedents and contingency factors for value creation in this service area are identified, and distinctive variations of the PSDL in healthcare contexts.…”
Section: Papers In This Issuementioning
confidence: 99%
“…Low health literacy also prevents the opportunity to fill the cognitive gaps that are produced by inadequate individual skills through the establishment of clear and comfortable relationships with the providers of care (Hironaka and Paasche-Orlow 2008). The side effects of inadequate health literacy are particularly significant for people suffering from multiple chronic conditions (Hardyman et al 2019). Studies have also shown that patients may be unwilling to participate in the provision of care due to the physical and psychological weaknesses that are associated with the illness (Arnetz et al 2008).…”
Section: Co-creation Value and The Importance Of Health Literacymentioning
confidence: 99%